Pilsbryiscalpellum parallelogramma - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
Pilsbryiscalpellum parallelogramma (Hoek, 1883) Fig. 21 Scalpellum parallelogramma Hoek, 1883: 83, pl. III, figs 15–16, pl. IX, figs 1–5; Weltner, 1897: 249; Gruvel, 1905: 61, fig. 67; Nilsson-Cantell, 1931: 8. Arcoscalpellum parallelogramma : Newman & Ross, 1971: 76–79, pl. IX, C, figs 37–38. Pilsbryiscalpellum parallelogramma : Zevina, 1981a: 214–215, fig. 152. Material examined. Eight syntypes NHM UK 2013.1103-1110, Stn 320: Atlantic, Southwest (off Rio La Plata, Argentina); 1097 m. Supplementary descriptions. Newman & Ross (1971) and Zevina (1981a). Distribution. Atlantic, Southwest. Known depth range 567 to 1097 m. Habitat. On Dendrophyllia corals. Genus Planoscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part). Planoscalpellum Zevina, 1978b: 1347. Diagnosis. Upper latus with umbo on scutal margin inframedian latus with umbo apical or sub-basal; carinal latus with umbo on carinal part, may be protruding. Type species. Scalpellum planum Hoek, 1883. Composition. Four species. Distribution. Worldwide, except polar areas. Known depth range 1301 to 6180 m. Genus Planoscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part). Planoscalpellum Zevina, 1978b: 1347. Diagnosis. Upper latus with umbo on scutal margin inframedian latus with umbo apical or sub-basal; carinal latus with umbo on carinal part, may be protruding. Type species. Scalpellum planum Hoek, 1883. Composition. Four species. Distribution. Worldwide, except polar areas. Known depth range 1301 to 6180 m. : Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS " Challenger " expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on pages 34-35, DOI: 10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932 : {"references": ["Hoek, P. P. C. (1883) Report on the Cirripedia collected by H. M. S. \" Challenger \" during the years 1873 - 1876. Systematic part. Report on the Scientific Results of the Voyage H. M. S. \" Challenger \", during the years 1873 - 7, Zoology, part 25 (8), 1 - 169.", "Weltner, W. (1897) Verzeichnis der bisher beschriebenen recenten Cirripedienarten. Mit Angabe der im berliner Museum vorhandenen Species und ihrer Fundorte. Archiv fur Naturgeschichte, 63 (1), 227 - 280.", "Gruvel, A. (1905) Monographie des Cirrhipedes ou Thecostraces. Masson et Cie (editeurs), Libraire de l'Academie de Medicine, Paris, 472 pp.", "Nilsson-Cantell, C. A. (1931) Cirripeds from the Indian Ocean and Malay Archipelago in the British Museum (Nat. Hist.), London. Arkiv fur Zoologie, Stockholm, 23 A (18), 1 - 12.", "Newman, W. A. & Ross A. (1971) Antarctic Cirripedia. Antarctic Research Series, 14. American Geophysical Union, Washington, 257 pp.", "Zevina, G. B. (1981 a) Cirriped crustaceans of the suborder Lepadomorpha (Cirripedia, Thoracica) of the World Ocean. Part 1. Family Scalpellidae. Opredeliteli po Faune SSSR, Leningrad, 398 pp. [in Russian]", "Hoek, P. P. C. (1907) The Cirripedia of the Siboga expedition A. Cirripedia Pedunculata. Siboga Expeditie Monographe, 31 (a), 1 - 127.", "Zevina, G. B. (1978 b) A new classification of the Scalpellidae (Cirripedia, Thoracica). Part 2 Subfamilies Arcoscalpellinae and Meroscalpellinae. Zoologicheskii Zhurnal, 57 (9), 1343 - 1352. [in Russian]"]}